Running quietly reduces ground reaction force and vertical loading rate and alters foot strike technique - Phan, X.; Grisbrook, Tiffany; Wernli, K.; Stearne, S.; Davey, Paul; Ng, Leo (Routledge, 2016)
This study aimed to determine if a quantifiable relationship exists between the peak sound amplitude and peak vertical ground reaction force (vGRF) and vertical loading rate during running. It also investigated whether differences in peak sound amplitude, contact time, lower limb kinematics, kinetics and foot strike technique existed when participants were verbally instructed to run quietly compared to their normal running. A total of 26 males completed running trials for two sound conditions: normal running and quiet running. Simple linear regressions revealed no significant relationships between impact sound and peak vGRF in the normal and quiet conditions and vertical loading rate in the normal condition. t-Tests revealed significant within-subject decreases in peak sound, peak vGRF and vertical loading rate during the quiet compared to the normal running condition. During the normal running condition, 15.4% of participants utilised a non-rearfoot strike technique compared to 76.9% in the quiet condition, which was corroborated by an increased ankle plantarflexion angle at initial contact. This study demonstrated that quieter impact sound is not directly associated with a lower peak vGRF or vertical loading rate. However, given the instructions to run quietly, participants effectively reduced peak impact sound, peak vGRF and vertical loading rate.